Analiza ispravnosti zvučne signalizacije viličara u Republici Srbiji - Gavanski, Dušan (Array, 2019)
The paper explains the terms “indoor transport” and “forklift“, and presents the types of lethal injuries that can occur when using forklifts. The methodology is presented that was used to analyse the proper functioning of sound signalling devices used on forklifts. The descriptive method based on a checklist was used.The research was conducted on 127 forklifts of average age 15 years. It was determined that about 50% forklifts did not have a properly functioning device that emits sound during driving in reverse. On about 25% forklifts, the sirens were not functioning properly. The results of the analysis are discussed and further courses of action are proposed.